Pengaruh Pelatihan dan Locus of Control terhadap Kinerja Pegawai di Dinas Pendidikan, Pemuda dan Olahraga Kabupaten Bantul - Muhamad Nasrip (Jurnal MANAJERIAL, 2023)
The purpose of this study was to examine the nature of the relationship between exercise and a person's sense of control in the context of the Dinas Pendidikan Pemuda dan Olahraga Kabupaten Bantul. Participants in this study were all active members of the ASN business, and used quantitative research techniques. The population in this study were ASN employees, with samples taken using the accidental sampling method, namely 30 respondents. The test uses multiple linear regression analysis data using the SPSS version 18 test tool. The results of this study indicate that there is an effect of training on employee performance with a significance value of 0.000, locus of control does not affect employee performance with a significance value of 0.925. The effect of training and locus of control on employee performance at the Dinas Pendidikan Pemuda dan Olahraga Kabupaten Bantul has a significant value of 0.000 and contributes 43.1% to variations or changes in performance. Since training and locus of control are two factors that may be directly influenced by employees, this value is important. Factors that cannot be controlled are the causes of the remaining 56.9%, so existing employees must further improve their performance capabilities starting from knowledge, skills and motivation.